Modeling the Dependence of Power Diode on Temperature and Radiation - S.M. El-Ghanam; A.M. Abd El-Maksood; F.A.S. Soliman (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
A theoretical study had been carried out on the effect of radiation on the electrical properties of silicon power diodes. Computer program "PDRAD2013" was developed to solve the diode equations and to introduce the operating conditions and radiation effects upon its parameters. Temperature increase interrupts the electrical properties of the diode in the direction of drop voltage decrease across the p-n junction.. The model was analyzed under the influence of different radiation type (gamma-rays, neutrons, protons and electrons) with various dose levels and energies. The carriers diffusion length were seriously affected leading to a large increase in the forward voltage. These effects were found to be function of radiation type, fluence and energy.